Diagnostic workup of cancer in patients with new-onset anaemia: a Danish cohort study in general practice. (2nd October 2021) - Boennelykke, Astrid; Jensen, Henry; Falborg, Alina Zalounina; Granfeldt Østgård, Lene Sofie; Hansen, Anette Tarp; Christensen, Kaj Sparle; Vedsted, Peter
Abstract: Background: Anaemia is associated with adverse outcomes, including increased morbidity and all-cause mortality. Diagnostic workup of patients with anaemia is essential to detect underlying disease, especially undiagnosed malignancy. Objective: To describe the cancer-relevant diagnostic workup in patients with new-onset anaemia detected in general practice. An additional aim was to analyse associations between patient characteristics and the diagnostic workup. Design: Observational population-based cohort study using electronic laboratory and register data. Setting: Danish general practice. Subjects: Patients aged 40–90 years with new-onset anaemia (no anaemia in the preceding 15 months) detected in general practice. Patients were identified in Danish laboratory information systems and nationwide registries in 2014–2018. Main outcome measures: We measured the proportion of patients receiving predefined diagnostic investigations, that is, cancer patient pathway, colonoscopy, gastroscopy, computerised tomography (CT) scan, faecal test for haemoglobin, and bone marrow examination within three months of the anaemia index date. Results: We included 59, 993 patients, and around half of the patients with 'iron deficiency anaemia', 'anaemia of inflammation', or 'combined inflammatory iron deficiency anaemia' had no cancer-relevant diagnostic investigations performed. Patients aged 60–79 years and patients with severe anaemia were more likely to have investigations performed, while patients with comorbidity were less likely to have investigations performed. Conclusion: Around half of the patients with anaemia subtypes that may indicate underlying cancer had no cancer-relevant diagnostic investigations performed. This may represent missed diagnostic opportunities. Future interventions are needed to improve the diagnostic workup of cancer in patients with anaemia, for example, laboratory alert systems and clinical decision support. KEY POINTS: The general practitioners are often the first to detect anaemia and its underlying disease (e.g. undiagnosed malignancy). Large-scale studies are needed on the diagnostic workup of patients with anaemia in general practice in relation to an underlying malignancy. This study shows that the majority of patients with anaemia had no cancer-relevant diagnostic investigations performed, which may cause diagnostic delay. Interventions seems needed to improve the diagnostic workup of cancer in these patients to ensure timely diagnosis.